Stimulated Raman Scattering in Routing and Wavelength Assignment / W. S. Sim ... [et al.] - W. S., Sim; S. C., Tan; Yusoff, Zulfadzli (2014)
In this paper, the implication of Stimulated Raman Scattering (SRS) in Routing and Wavelength Assignment (RWA) is investigated by analyzing the SRS parameters that related to RWA and its capabilities of influence the network performance. It then followed by identifying the necessary SRS parameters that must be followed in RWA to minimize the effect of SRS